2017
DOI: 10.1038/s41598-017-07867-5
|View full text |Cite
|
Sign up to set email alerts
|

Long-range spontaneous droplet self-propulsion on wettability gradient surfaces

Abstract: The directional and long-range droplet transportation is of great importance in microfluidic systems. However, it usually requires external energy input. Here we designed a wettability gradient surface that can drive droplet motion by structural topography. The surface has a wettability gradient range of over 150° from superhydrophobic to hydrophilic, which was achieved by etching silicon nanopillars and adjusting the area of hydrophilic silicon dioxide plane. We conducted force analysis to further reveal the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
127
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(129 citation statements)
references
References 52 publications
1
127
1
Order By: Relevance
“…The wettability gradients can drive droplet transport direction due to the microstructures in the surface [ 39 , 40 ]. The diameters of non-uniformly distributed cylindrical micro pillars range from 70 μm to 150 μm with about 10 μm height.…”
Section: Resultsmentioning
confidence: 99%
“…The wettability gradients can drive droplet transport direction due to the microstructures in the surface [ 39 , 40 ]. The diameters of non-uniformly distributed cylindrical micro pillars range from 70 μm to 150 μm with about 10 μm height.…”
Section: Resultsmentioning
confidence: 99%
“…Previous work has demonstrated that surface structure and, more specifically, surface microstructure can also be exploited to finely tune the surface wettability, thus creating an alternative method to activate droplet motion. [20][21][22][23][24][25][26] Compared to the methods above, making use solely of surface structure with a uniform chemical coating or structuring an intrinsically hydrophobic material provide advantages such as chemical stability, robustness and precise wettability adjustment without the need for external disturbances, making it an ideal choice as microfluidic systems.…”
Section: Take Down Policymentioning
confidence: 99%
“…The motion of a liquid droplet sitting in the Cassie-Baxter (CB) state 27 on intrinsically hydrophobic microstructures with small hysteresis can be induced by a roughness gradient towards the region where its (effective) free surface energy is lower, once it has overcome hysteresis. [21][22][23]26 Additionally, external forces such as vibrations and coalescence have been exploited to overcome droplet adhesion and/or hysteresis in the presence of micropillars, 23,24 since otherwise the motion is limited. 22 However, spontaneous movement can be achieved on micro-striations with high length to width aspect ratio, for a much longer distance with only the help of the initial deposition energy and roughness gradient.…”
Section: Take Down Policymentioning
confidence: 99%
“…The fabrication accuracy and morphology of the structures at the nanoscale were evaluated by measuring the distance between the micropillars and their diameter by scanning electron microscopy Silicon-based nanostructures exhibit conceivable applications in several fields. As examples, plasmonic nanostructures based on array of silicon nanopillars could be used for surface enhanced Raman spectroscopy (SERS) or to control the wettability of a silicon surface [44][45][46][47]. Silicon micropillar arrays can be assembled by lithographic techniques allowing tight control over the size and density of the micropillars, differently from randomly generated rough surfaces as those presented in several other works [17,43,48,49].…”
Section: Slide Code Pillar Diameter (μM) Distance Among Pillars (μM) mentioning
confidence: 99%